SUPPORTING AND INHIBITING FACTORS OF THE ADIWIYATA PROGRAM AT SMA 78 JAKARTA VIEWED FROM THE PERSPEKTIVE OF PIERRE BOURDIEU'S THEORY - Zainina, Hasny Ainun; Malihah, Elly; Wilodati, Wilodati (Universitas Negeri Medan, 2024)
The environment is a very important aspect for human life. However, currently various environmental problems in Indonesia continue to emerge and even represent urgent problems. One of the contributing factors is bad community behavior patterns. One alternative to overcome this problem is to habituate environmentally caring behavior in schools. The aim of this research is to analyze what are the driving and inhibiting factors for the adiwiyata program at SMA 78 Jakarta, especially since this school is a school with independent adiwiyata status from 2017 to 2023. This research was conducted using a quantitative approach using the case study method. The data collection techniques used were observation, interviews and documentation studies. Meanwhile, the data analysis techniques used are reduction, data display, drawing conclusions and verification. Interviews were conducted with the head of Adiwiyata at SMA 78, the deputy head of the school for student affairs, 5 teachers and 2 students. The research results show that the success of the adiwiyata program at SMA 78 is driven by the habitus, capital and field at SMA 78 which are in harmony with the adiwiyata program. Meanwhile, the inhibiting factors for the adiwiyata program at SMA 78 are more due to the environment-based lifestyle at the school which is still expensive and difficult to obtain and not all school residents come from environments that previously implemented adiwiyata so that when they enter SMA 78 they are not used to it. SMA 78 needs to be consistent in providing a conducive field regarding adiwiyata at school so that the habitus of all school members can be well formed.